Proposal for Integration of Circular Economy Within Product Portfolio Management - Jugend, Daniel [UNESP] (2022)
Although current studies are pointing to the circular economy (CE) as one of the main trends for sustainable production and consumption systems, little is known about its applicability within new product development (NPD). In particular, there is a lack of studies connecting CE to product portfolio decision in early stages of the NPD process. Through a systematic literature review, this study aims to propose a framework that integrates CE practices and methods into product portfolio management (PPM). In combination with the well-known and traditional methods of PPM literature, the framework presented introduces the use of CE-based practices and methods to analyse the potential of product design concerning aspects such as durability, reuse, upgrading, remanufacturing, recyclability, recovery, and product service system. The proposed framework presents theoretical and managerial implications by sharing management methods and practices towards a product portfolio aligned with the principles of circularity.